Avaliação de relacionamentos no canal de distribuição de produtos de mercearia básica. - Pigatto, Gessuir (2005)
The shift of power inside distribution channels and the need for adapting to constant consumer market changes have led enterprises to seek alternatives in order to face that new environment. Suppliers pursue to adapt themselves to the increasing power of large retail groups, while the latter need to adapt themselves to the growth of business networks composed by the small and medium grocery retailers and to the strengthening of independent stores and other distribution channels. At the same time, worldwide economy gives importance to the idea that all links of a supply chain must work in a collaborative integrated way, aiming gains in efficiency and productivity, and avoiding losses and rework. Thus, it is necessary to change enterprises relationships, in which conflict and bargaining power can be replaced by cooperation. However, it is important to understand the reasons leading to a collaborative business relation program. Also, it is necessary to comprehend expectations of both sides in the relation, as well as to understand how companies check whether such expectations have been reached or not. Therefore, the main objective of this research was to identify the most important behavioral variables in collaborative relations. From those variables, it was proposed parameters (actions and behaviors) which might be used by self-service retail companies and by their grocery suppliers, in order to evaluate the results of adopting new relation patterns noticed in the sector. To accomplish the research, 10 small and medium-sized retail groups, located in the state of São Paulo, and 10 grocery suppliers, indicated by the former, were interviewed. The analysis of results has showed that Trust and Compromising are the most important behavioral variables for retail groups and grocery suppliers. Additionally, less important variables for both samples were Power, Dependency and Conflict, the least important of all. The analysis of behavioral variables has showed consistency with theoretical inferences. However, most companies didn t use parameters to evaluate the development of those relations. From answers given by the interviewees and from the review of theory, it was possible to create two instruments for evaluating relationships. The first one is Behavioral Variable Maps. Through those maps it is possible to visualize partners actions and behaviors. Hence, it is possible to identify in which aspects those partners get closer to a collaborative relationship, and which actions and behaviors still need to be improved in order to achieve the results of collaborative relationships. The second evaluation instrument is a 2X2 Matrix, through which collaborative relationships are evaluated.